Score-line effect on work-rate in English FA Premier League soccer - O'Donoghue, P.; Robinson, G. (International Journal of Performance Analysis in Sport, 2016)
This paper investigates the effect of score-line on work-rate in English FA Premier League soccer. Player movement data from 110 matches where a goal was scored between 15 minutes and the end of the first half were captured by the ProzoneTM player tracking system. The number of V-cut path changes performed per minute declined more after the first goal in matches that were won by one of the sides than in drawn matches